Functional neuroanatomy of antisaccade eye movements investigated with positron emission tomography. - O'Driscoll, G A (1995)
Increasing interest in the role of the frontal lobe in relation to psychiatric and neurologic disorders has popularized tests of frontal function. One of these is the antisaccade task, in which both frontal lobe patients and schizophrenics are impaired despite normal performance on (pro)saccadic tasks. We used position emission tomography to examine the cerebral blood flow changes associated with the performance of antisaccades in normal individuals. We found that the areas of the brain that were more active during antisaccades than saccades were highly consistent with the oculomotor circuit, including frontal eye fields (FEFs), supplementary motor area, thalamus, and putamen. Superior parietal lobe and primary visual cortex were also significantly more active. In contrast, prefrontal areas 46 and 9 were not more active during antisaccades than during saccades. Performance of some frontal patients on the antisaccade task has been likened to a bradykinesia, or the inability to initiate a willed movement. It is the necessity to will the movement and inhibit competing responses that intuitively linked this task to the dorsolateral prefrontal cortex in frontal patients. Our data suggest that it is the FEFs in prefrontal cortex that differentiate between conditions in which the required oculomotor response changes while the stimulus remains the same, rather than areas 46 and 9, which, in human studies, have been linked to the performance of complex cognitive tasks. Such a conclusion is consistent with single-unit studies of nonhuman primates that have found that the FEFs, the executive portion of the oculomotor circuit, can trigger, inhibit, and set the target of saccades.